Pengaruh Oksidasi Setelah Deposisi Terhadap Sifat Film Tipis ZnO:Ga - Faizal, Reza; Marwoto, Putut; Sulhadi, Sulhadi; Sugianto, Sugianto (Jurnal Matematika dan Sains, 2017)
The effect of after-deposition oxidation to the thin film properties Ga doped ZnO has been studied.  Film deposited using dc magnetron sputtering method at temperature 300oC for one hour and then it was performed variations of oxidation using oxygen gas (99,9%) with pressure of 0 mTorr and 50 mTorr at a temperature of 300 ° C for 20 minutes. According to the image scanning of electron microscopy, it shows that the film grain size became larger in oxygen pressure of 50 mTor as compared to the pressure of 0 mTor. UV-Vis spectrophotometer analysis showed the film transmittance in visible light increases with the increasing of oxygen pressure reached ~83%. Band-gap energy that has been produced by film on the oxygen pressure of 0 mTorr and 50 mTorr are respectively 3.32 eV and 3.4 eV.